Fifty years after the penitentiary reform: Between betrayed expectations and unresolved issues - Latella, Davide (Form@re - Open Journal per la formazione in rete, 2025)
The 1975 prison reform represented a turning point in the Italian prison system, establishing constitutional principles in the penal execution and recognising prisoners as legal entities with rights and guarantees. The preference for legislation over regulations strengthened the conceptual autonomy of prison law and gave the supervisory judiciary central functions. However, the ambitious reform plan was thwarted by the inertia of the physical structures, the persistence of security-based thinking and the legacy of paternalistic views. The result was a fragmented and incomplete implementation, which still today calls for a renewed systemic rethinking of the prison system in order to fully achieve the goal of rehabilitation. Cinquant’anni dopo la riforma penitenziaria: tra aspettative tradite e nodi irrisolti. La riforma penitenziaria del 1975 ha rappresentato una svolta epocale nel panorama detentivo italiano, sancendo l’ingresso dei principi costituzionali nell’esecuzione penale e riconoscendo al detenuto una soggettività giuridica dotata di prerogative e garanzie. L’opzione per lo strumento legislativo, in luogo di quello regolamentare, ha rafforzato l’autonomia concettuale del diritto penitenziario e conferito alla magistratura di sorveglianza funzioni centrali. Tuttavia, l’ambizioso disegno riformatore si è infranto contro l’inerzia delle strutture materiali, la persistenza di logiche securitarie e il retaggio di visioni paternalistiche. Ne è derivata un’applicazione frammentaria e incompiuta, che ancora oggi reclama un rinnovato ripensamento sistemico dell’apparato penitenziario per una piena attuazione del finalismo rieducativo.